Influence of infant feeding and gluten intake on coeliac disease. Issue 2 (1st February 1997) - Ascher, H; Krantz, I; Rydberg, L; Nordin, P; Kristiansson, B
Abstract : OBJECTIVES: To study the impact of infant feeding habits and actual gluten intake on gluten induced enteropathy. METHODS: A case-referent design, controlling for the HLA alleles conferring increased genetic risk, was used. All 164 siblings of 97 probands were investigated. Eighty five of the siblings, carrying the genes DQA1*0501-DQB1*02 conferring susceptibility for the disease, were investigated by interview, food recording, and taking a small intestinal biopsy sample. Eight cases of silent coeliac disease were found and these were compared with the 73 siblings in whom the diagnosis was excluded. RESULTS: No statistically significant differences were found between cases and referents in terms of duration of breast feeding, age at introduction of cows' milk products, frequency of breast feeding after gluten introduction, and gluten consumption. CONCLUSIONS: The studied factors may be of less importance for the development of gluten induced enteropathy.